A plant Bcl-2-associated athanogene is proteolytically activated to confer fungal resistance - Mehdi Kabbage; Ryan Kessens; Martin B. Dickman (Microbial Cell)
The Bcl-2-associated athanogene (BAG) family is a multifunctional group of proteins involved in numerous cellular functions ranging from apoptosis to tumorigenesis. These proteins are evolutionarily conserved and encode a characteristic region known as the BAG domain. BAGs function as adapter proteins forming complexes with signaling molecules and molecular chaperones. In humans, a role for BAG proteins has been suggested in tumor growth, HIV infection, and neurodegenerative diseases; as a result, the BAGs are attractive targets for therapeutic interventions, and their expression in cells may serve as a predictive tool for disease development. The Arabidopsis genome contains seven homologs of BAG family proteins (Figure 1), including four with a domain organization similar to animal BAGs (BAG1-4). The remaining three members (BAG5-7) contain a predicted calmodulin-binding motif near the BAG domain, a feature unique to plant BAG proteins that possibly reflects divergent mechanisms associated with plant-specific functions. As reported for animal BAGs, plant BAGs also regulate several stress and developmental processes (Figure 2). The recent article by Li et al. focuses on the role of BAG6 in plant innate immunity. This study shows that BAG6 plays a key role in basal plant defense against fungal pathogens. Importantly, this work further shows that BAG6 is proteolytically activated to induce autophagic cell death and resistance in plants. This finding underscores the importance of proteases in the execution of plant cell death, yet little is known about proteases and their substrates in plants.